Structure-activity relationships of dually-acting acetylcholinesterase inhibitors derived from tacrine on N-methyl-d-Aspartate receptors - Gorecki, Lukas; Misiachna, Anna; Damborsky, Jiri; Dolezal, Rafael; Korabecny, Jan; Cejkova, Lada; Hakenova, Kristina; Chvojkova, Marketa; Karasova, Jana Zdarova; Prchal, Lukas; Novak, Martin; Kolcheva, Marharyta; et al. (European journal of medicinal chemistry, 2021)
Tacrine is a classic drug whose efficacy against neurodegenerative diseases is still shrouded in mystery. It seems that besides its inhibitory effect on cholinesterases, the clinical benefit is co-determined by NMDAR-antagonizing activity. Our previous data showed that the direct inhibitory effect of tacrine, as well as its 7-methoxy derivative (7-MEOTA), is ensured via a "foot-in-the-door" open-channel blockage, and that interestingly both tacrine and 7-MEOTA are slightly more potent at the GluN1/GluN2A receptors when compared with the GluN1/GluN2B receptors. Here, we report that in a series of 30 novel tacrine derivatives, designed for assessment of structure-activity relationship, blocking efficacy differs among different compounds and receptors using electrophysiology with HEK293 cells expressing the defined types of NMDARs. Selected compounds (4 and 5) potently inhibited both GluN1/GluN2A and GluN1/GluN2B receptors; other compounds (7 and 23) more effectively inhibited the GluN1/GluN2B receptors; or the GluN1/GluN2A receptors (21 and 28). QSAR study revealed statistically significant model for the data obtained for inhibition of GluN1/Glu2B at -60 mV expressed as IC50 values, and for relative inhibition of GluN1/Glu2A at +40 mV caused by a concentration of 100 μM. The models can be utilized for a ligand-based virtual screening to detect potential candidates for inhibition of GluN1/Glu2A and/or GluN1/Glu2B subtypes. Using in vivo experiments in rats we observed that unlike MK-801, the tested novel compounds did not induce hyperlocomotion in open field, and also did not impair prepulse inhibition of startle response, suggesting minimal induction of psychotomimetic side effects. We conclude that tacrine derivatives are promising compounds since they are centrally available subtype-specific inhibitors of the NMDARs without detrimental behavioral side-effects.
Keywords: kvantitativní vztahy mezi strukturou a aktivitou; Mice, Inbred ICR; receptory N-methyl-D-aspartátu; membránové potenciály; Electrophysiology; Rats; Acetylcholinesterase; Butyrylcholinesterase; Blood-Brain Barrier; cholinesterasové inhibitory; acetylcholinesterasa; psi; butyrylcholinesterasa; takrin; rekombinantní proteiny; Dogs; Tacrine; Cholinesterase Inhibitors; mužské pohlaví; Rats, Wistar; Receptors, N-Methyl-D-Aspartate; Mice; Recombinant Proteins; Glutamate receptor; Membrane Potentials; krysa rodu Rattus; poločas; Quantitative Structure-Activity Relationship; Locomotion; zvířata; Humans; racionální návrh léčiv; myši inbrední ICR; Half-Life; myši; potkani Wistar; Drug Design; hematoencefalická bariéra; Pharmacology; Ion channel; lokomoce; in vivo; QSAR; lidé; Male; Animals